The Role of Diversity, Equity, and Inclusion on Leadership Succession: An Empirical Study with the Mediating Roles of Employee Performance and Employee Engagement - Vincent Vincent; Christian Haposan Pangaribuan (PT Publikasiku Academic Solution, 2025)
In the era of BANI (Brittle, Anxious, Non-Linear, Incomprehensible), organizations face increasingly complex and rapidly changing challenges. Leadership sustainability is an important element for organizations to be able to compete and develop their business sustainably. Organizations can increase the implementation of leadership succession through the creation of a work environment that supports the identification and development of future leaders. This study aims to analyze the influence of diversity, equity, and inclusion on the effectiveness of leadership succession by considering the mediating role of employee performance and engagement. The background of this research is based on the weak implementation of DEI principles in many organizations, which often results in social conflict, discrimination, and low participation and motivation of an employee. This study uses a non-experimental quantitative approach. Data was obtained through research instruments in the form of surveys developed from various previous studies and aimed at employees from various backgrounds in Indonesia, then analyzed using Structural Equation Modeling (SEM) techniques based on Partial Least Squares (PLS). The results of the study are expected to make an empirical contribution in explaining the relationship between the implementation of DEI and leadership succession through employee performance and engagement. The findings in this study are expected to be input for human resource management when designing more inclusive and adaptive leadership development strategies. This study is also expected to close the gap in the literature by mapping the causal relationship between DEI variables, employee performance, employee engagement, and leadership succession in the context of organizations in Indonesia